Association and Expression Analyses of the Duck FMO3 Gene in Relation to Fatty Acid Composition - Anggraeni; Gunawan, Asep; Rukmiasih; Suryati, Tuti; Sumantri , Cece (International Journal of Poultry Science, 2017)
Background and Objective: Flavin containing monooxygenase 3 (FMO3) is an excellent candidate gene that affects fishy odor and fatty acid composition. It has been reported that down regulation of FMO3 can inhibit fatty acid oxidation. The aim of this study was to investigate the association and expression of the FMO3 gene as a candidate gene for fatty acid composition in Indonesian Cihateup ducks. Methodology: A total of one hundred Indonesian Cihateup ducks were used in this study. Tissues from breast muscles were used for genomic DNA isolation and fatty acid composition analysis. Results: Association analysis showed that the SNP g.849A>G was significantly associated with unsaturated fatty acids (palmitoleic, oleic, linoleic, linolenic and arachidonic acid) and saturated fatty acids (lauric, palmitic and arachidic acid). Compared to the GG genotype, the AG genotype ducks exhibited greater levels (p<0.05) of lauric acid (C14:0), palmitic acid (C16:0), arachidonic acid (C20:4n6) palmitoleic acid (C16:1), oleic acid (C18:1), linolenic acid (C18:3) and linoleic acid (C18:2, p<0.05) but not pentadecanoic acid (C15:0). Furthermore, to analyze the mRNA expression of FMO3 in liver tissues, the ducks were divided into two groups according to the genotypes AG and GG, where AG had relatively favourable unsaturated fatty acid composition. FMO3 mRNA expression was higher (p<0.01) in animals with the AG genotype. Conclusion: These results will improve the understanding of functions of the FMO3 gene in maintaining muscular fatty acid composition and will shed light on FMO3 as a candidate gene in the selection of ducks with unsaturated fatty acids for meat quality improvement.